vault backup: 2025-02-16 19:37:21
This commit is contained in:
parent
d2ffd42b20
commit
f5a2d9f90e
@ -28,7 +28,13 @@ The above formula can be used to find the *derivative*. This may also be referre
|
|||||||
$$ y - y_1 = m(x-x_1) $$
|
$$ y - y_1 = m(x-x_1) $$
|
||||||
Given that $m = f'(a)$ and that $(x_1, y_1) = (a, f(a))$, you get the equation:
|
Given that $m = f'(a)$ and that $(x_1, y_1) = (a, f(a))$, you get the equation:
|
||||||
$$ y - f(a) = f'(a)(x - a) $$
|
$$ y - f(a) = f'(a)(x - a) $$
|
||||||
As a more practical example, given an equation with a slope of $6$,
|
As a more practical example, given an equation with a slope of $6$ at the point $(-2, -4)$:
|
||||||
|
$$ y - (-4) = 6(x - -2)$$
|
||||||
|
Solving for $y$ looks like this:
|
||||||
|
1. $y + 4 = 6(x + 2)$
|
||||||
|
2. $y = 6(x + 2) - 4$
|
||||||
|
3. $y = 6x + 12 - 4$
|
||||||
|
4. $y = 6x + 8$
|
||||||
# Line Types
|
# Line Types
|
||||||
## Secant Line
|
## Secant Line
|
||||||
A **Secant Line** connects two points on a graph.
|
A **Secant Line** connects two points on a graph.
|
||||||
@ -123,9 +129,9 @@ $$ \dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x) $$
|
|||||||
> Given the function $(x^2+3)^4$, find the derivative.
|
> Given the function $(x^2+3)^4$, find the derivative.
|
||||||
|
|
||||||
Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$.
|
Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$.
|
||||||
6. First find the derivative of the outside function function ($f(x) = x^4$):
|
5. First find the derivative of the outside function function ($f(x) = x^4$):
|
||||||
$$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 ...$$
|
$$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 ...$$
|
||||||
7. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$.
|
6. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$.
|
||||||
$$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$
|
$$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$
|
||||||
> Apply the chain rule to $x^4$
|
> Apply the chain rule to $x^4$
|
||||||
|
|
||||||
@ -161,8 +167,8 @@ $$ \dfrac{d}{dx} \cot x = -\csc^2 x $$
|
|||||||
- Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$.
|
- Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$.
|
||||||
|
|
||||||
Given these facts:
|
Given these facts:
|
||||||
8. Let $y$ be some function of $x$
|
7. Let $y$ be some function of $x$
|
||||||
9. $\dfrac{d}{dx} x = 1$
|
8. $\dfrac{d}{dx} x = 1$
|
||||||
10. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\
|
9. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\
|
||||||
|
|
||||||
## Examples
|
## Examples
|
||||||
|
Loading…
x
Reference in New Issue
Block a user